Educação infantil pensamentos contemporâneos - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
The resulting transformations in the political-scientific panorama have shaped conceptions about children and childhood, which, in the current situation, is understood as a complex human being who experiences specific moments in their existence, an occasion in which accelerated processes allow their insertion into the social and historical environment. Based on these premises, the text presented here seeks to verify contemporary thinking about early childhood education through an integrative review of the literature through the interactive magazine Education and Society, having as its objective the purpose of discussing the importance of establishing the Early Childhood Education, its political-pedagogical role, and its legitimization with regard to the concerns of the current universe. The research is justified by the need to reflect on pedagogical practices and training of educators in promoting methods capable of guaranteeing conditions and possibilities for creating new things in comparison to old trends. To understand the historical evolution of this advance, we resort to the main research that has been carried out in the Brazilian territory within the magazine Education and Society in the time frame from 2000 to 2023. We used the literature review tool that would be described as a of detailed analysis on a given theoretical field. To strengthen reflection, the legal frameworks that legitimize Early Childhood Education as a right and endorse it within the scope of educational policies are also presented. Through the research, it was observed that there had been some advances in the children's educational scenario, from the right of children aged 0 to 6 to attend daycare centers and preschools to the creation of the framework that guides this stage of education, with some reflection on these advances and to what extent they address the needs of children without differences in care based on the class to which they belong
Keywords: Educação Infantil; Direitos e deveres; Esferas educacionais; CNPQ:: CIÊNCIAS HUMANAS